Electroless deposition of aluminium alloy LM25 by SiC and Ni-P nano coating. (2021) - Vetrivezhan, P.; Ayyanar, C.; Arunraj, P.V.; Vasanthkumar, P.; Ganesan, D.
Abstract: Recent researchers developed unique materials by the method of electroless coating for the various industrial applications. Electroless coating is a simple way to produce various metals with high impact and enhanced mechanical properties. In this article an experimental investigation on optimizing characteristics parameters of electroless coating of Nickel-Phosphorous and Silicon carbide nano coating on aluminium alloy LM25. A comprehensive experimental characterization of electroless nickel-phosphorous coating and Silicon carbide nano coating on aluminium alloy LM25 under specific coating conditions is reported. At present nickel –phosphorous and Silicon carbide was coated over aluminium alloy LM25 using electroless coating method. The surfactant SLS was added into solution before EN deposition. The stabilizer thiourea (1 ppm) was added into the bath when the reaction is stable. Characterization parameters such as pH and Temperature were varied and the corresponding coating thickness, rate of deposition, surface roughness and microhardness were to be measured. The level of pH and Temperature varied and their influence on coating process was studied. An observed value of pH in the range of 4–5, 6–7, 8–9 and observed temperature was diversely at different values such as 70 °C, 85 °C, and 90 °C. The result showed that the coating thickness and microhardness was maximum when pH was 6–7, temperature was 85 °C. Scanning electron microscope was imaged a surface morphology of aluminium alloy LM25.